CANTÓN MAYO, I., CAÑÓN RODRÍGUEZ, R. y GRANDE DE PRADO, M. (Coords.). (2020). "Diseño de mejoras educativas: formación, gestión del conocimiento y tecnología". Murcia: EDIT.UM, 340 páginas, ISBN 978-84-17865-76-4 - José Luís Muñoz Moreno (Universidad de La Rioja, 2022)
CANTÓN MAYO, I., CAÑÓN RODRÍGUEZ, R. y GRANDE DE PRADO, M. (Coords.). (2020). Diseño de mejoras educativas: formación, gestión del conocimiento y tecnología. Murcia: EDIT.UM, 340 páginas, ISBN 978-84-17865-76-4